To switch or not to switch: Individual differences in executive function and emotion regulation flexibility - TOH, Wei Xing (Institutional Knowledge at Singapore Management University, 2021)
Emotion regulation (ER) constitutes strategies that modulate the experience and expression of emotions. While past work has predominantly focused on each ER strategy independently, recent research has begun to examine individual-difference factors that are associated with the flexible implementation of ER strategies in line with environmental demands (i.e., ER flexibility). Considering that ER processes generally implicate executive function (EF)—a collection of adaptive, general-purpose control processes—it is plausible that EF could be involved in ER flexibility. Using a latent-variable approach based on a comprehensive battery of EF tasks, the present study investigated how the various aspects of EF (i.e., common EF, working-memoryspecific, and shifting-specific factors) are related to the flexible maintenance and switching of ER strategies in response to stimuli that elicit varying levels of emotional intensity. Results indicated that better working-memory-specific ability (i.e., the ability to manipulate and update information within a mental workspace) was associated with greater ER strategy variability and higher frequency of ER strategy switching in high-, relative to low-, intensity contexts. Further, more proficient common EF (i.e., the ability to sustain relevant goals in the face of competing goals and responses) corresponded to greater propensity to maintain ER strategy for contexts with low-, but not high-, negative intensity. The outcomes of this study offer a richer understanding of the cognitive mechanisms underlying ER flexibility.